2019
DOI: 10.3390/jcm9010109
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Some Flavonoids and Organic Acids Widely Distributed in Plants

Abstract: Among natural substances widespread in fruits, vegetables, spices, and medicinal plants, flavonoids and organic acids belong to the promising groups of bioactive compounds with strong antioxidant and anti-inflammatory properties. The aim of the present work was to evaluate the antibacterial activity of 13 common flavonoids (flavones, flavonols, flavanones) and 6 organic acids (aliphatic and aromatic acids). The minimal inhibitory concentrations (MICs) of selected plant substances were determined by the micro-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
238
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 359 publications
(250 citation statements)
references
References 87 publications
(146 reference statements)
7
238
1
4
Order By: Relevance
“…Amongst other flavones widely distributed in fruits, plants, and spices, chrysin and apigenin showed moderate or low antimicrobial properties against Escherichia coli, Pseudomonas aeruginosa, Enterococcus faecalis, and Staphylococcus aureus, the Gram-negative bacteria being more susceptible to the natural compounds. Interestingly, the presence of hydroxyl groups in the phenyl rings A and B did not influence their activity, with the exception of Staphylococcus aureus [91]. On the contrary, Echeverría et al [92] reported that methylation of one hydroxyl group decreased the activity in 3-O-methylgalangin, and methylation of both hydroxyl groups caused inactivation against Bacillus subtilis and Escherichia coli.…”
Section: Antimicrobial and Antiviral Effect Of Citrus Flavonesmentioning
confidence: 96%
“…Amongst other flavones widely distributed in fruits, plants, and spices, chrysin and apigenin showed moderate or low antimicrobial properties against Escherichia coli, Pseudomonas aeruginosa, Enterococcus faecalis, and Staphylococcus aureus, the Gram-negative bacteria being more susceptible to the natural compounds. Interestingly, the presence of hydroxyl groups in the phenyl rings A and B did not influence their activity, with the exception of Staphylococcus aureus [91]. On the contrary, Echeverría et al [92] reported that methylation of one hydroxyl group decreased the activity in 3-O-methylgalangin, and methylation of both hydroxyl groups caused inactivation against Bacillus subtilis and Escherichia coli.…”
Section: Antimicrobial and Antiviral Effect Of Citrus Flavonesmentioning
confidence: 96%
“…These niosomes showed higher hepatoprotective effect compared to free quercetin in vivo, measuring serum biomarker enzymes (i.e., alanine and aspartate transaminases (ALT and AST)) and serum biochemical parameters (i.e., alkaline phosphatase (ALP) and total proteins), while following the histopathological investigation. This study confirms the ability of quercetin loaded niosomes to reverse CCl 4 intoxication and to carry out an antioxidant effect.Pharmaceutics 2020, 12, 143 2 of 18 and anticancer activities [1][2][3]. These intrinsic properties, together with their biocompatibility and remarkable antioxidant activity, have attracted researchers' attention to explore potential therapeutic applications [4,5].Quercetin (3, 30, 4, 5, 7-pentahydroxyflavone) is probably the most studied bioflavonoid, belonging to the family of flavonols; its therapeutic applications include hepatoprotection [6], prevention of neural cell apoptosis [7] and cancer chemo-prevention and treatment [8].Quercetin acts as strong antioxidant by scavenging free radicals and transition metal ions, thus decreasing the process of lipid peroxidation, which is responsible for the development of many diseases, e.g., cardiovascular and neurodegenerative diseases, as well as liver damage [9][10][11].However, quercetin therapeutic applications present challenges due to (i) low aqueous solubility, (ii) photo and oxidative degradability, (iii) high first-pass effect, (iv) poor intestinal absorption and, hence, low systemic bioavailability [12][13][14][15].In order to overcome these problems, which are common among flavonoids, drug delivery systems (DDS) including emulsions, cyclodextrins, polymeric nanoparticles, micelles and liposomes have been used to enhance their pharmaceutical properties [16][17][18].Out of various DDS, niosomes are similar to liposomes in structures, preparation techniques, and physical properties.…”
mentioning
confidence: 99%
“…Pharmaceutics 2020, 12, 143 2 of 18 and anticancer activities [1][2][3]. These intrinsic properties, together with their biocompatibility and remarkable antioxidant activity, have attracted researchers' attention to explore potential therapeutic applications [4,5].…”
mentioning
confidence: 99%
“…Presently, a rapid increase in the number of studies on medicinal plants due to presence of phenolic, avonoid, and phenolic acid compounds which have been observed owing to antioxidant and antibacterial activities (35). These phytochemical contents diverge depending on the plant's species, tissue, developmental stage, and environmental factors, such as temperature, water stress, and light conditions (3,36).…”
Section: Discussionmentioning
confidence: 99%
“…Mostly avonoids occur as aglycones and glycosylated and methylated derivatives, while glycosylated avonoids are abundant in the human daily diet (41)(42)(43). Moreover, avonoid makes a complex with extracellular or soluble proteins of bacterial cell walls (lipophilic) and may also disrupt bacterial membrane (35,44). Our results showed that both extracts contained much quantity of avonoid contents but CR extract (183.60 ± 4.06), has higher capacity as compared to VS (101.24 ± 2.09).Furthermore, another method is the DPPH-assay, based on the principle that any substance capable of donating hydrogen/an electron, so antioxidant potency is veri ed through DPPH method.…”
Section: Discussionmentioning
confidence: 99%